Implementasi Program Magrib Mengaji Sebagai Upaya Peningkatan Literasi Al-Qur’an Pada Anak Di Desa Pematang Johar - Khairani, Aulia (Journal of Community Sustainability, 2026)
The ability to read the Qur’an is a fundamental skill for Muslim children. However, in Pematang Johar Village, many children still face difficulties such as not recognizing Arabic letters, stammering while reading Iqra’, or lacking fluency in reciting the Qur’an. To address these challenges, a community service program titled Magrib Mengaji (Evening Qur’an Reading Program) was implemented for ten days by students of the Community Service Program (Kuliah Kerja Nyata or KKN) from Universitas Muhammadiyah Sumatera Utara in Pematang Johar Village. The activity involved approximately fifteen participants, ranging from elementary to junior high school students. The main focus of this program was to enhance Qur’anic reading skills through the talaqqi method and gradual learning tailored to each child’s ability. The implementation showed significant improvement among the children, particularly in recognizing Arabic letters, improving Iqra’ reading fluency, and refining Qur’anic recitation to become more tartil (properly rhythmic). Moreover, the program successfully fostered children’s enthusiasm for learning and strengthened community involvement in promoting Qur’anic literacy. This initiative demonstrates that strengthening Qur’anic literacy can be effectively achieved through collaborative efforts involving students, families, and the local community.